Caracterização do papel do mGluR5 no processo inflamatório associado à Doença de Huntington - Toniana Gonçalves de Carvalho (2018)
Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder characterized by involuntary movements, psychiatric and cognitive disorders leading ultimately to death. The cause of HD is an expanded polyglutamine (CAG) repeat in the exon 1 of the gene encoding the huntingtin protein. The number of CAG repeats is a major factor determining disease onset and gravity. HD affects certain brain areas with the death of neurons especially taking place in the striatum and neocortex. In addition to neurodegeneration, other events such as neuroinflammation seem to contribute to HD pathology. Both increased infiltration of immune cells and inflammatory cytokines have already been seen in post-mortem brains of HD patients. The metabotropic glutamate 5 receptor (mGluR5) plays a role in the regulation of intracellular pathways that were shown to be altered in HD and plays a dynamic role in the regulation of gene expression. The aim of this study was to evaluate whether mGluR5 also plays a role in the inflammatory process associated with HD. For this, the deletion of the mGluR5 gene was performed in a mouse model of HD (BACHD). Our results showed an increase in the number of microglia and astrocytes in the cortex of BACHD, mGluR5 -/- and BACHD/mGluR5 -/- mice at 12 months of age. In addition, neurodegeneration was observed in the cortex and striatum of BACHD, mGluR5 -/- and BACHD/mGluR5 -/- animals at 12 months of age. On the other hand, no changes in the inflammatory cytokine profile were observed in these animals. However, fractalkine or CX3CL1 was significantly less expressed in the cortex of BACHD/mGluR5 -/- mice at 12 months of age, as compared to control mice, which demonstrates its participation in the events associated with neuroinflammation. In addition, the mGluR5 antagonist MPEP was able to increase the expression of CX3CL1 in primary cortical neuronal culture. Taken together, the studies presented here indicate that mGluR5 participates in the inflammatory processes that take place in HD. Therefore, these results highlights the importance to elucidate the neuroinflammatory pathways that can be modified through mGluR5.